In vivo and in vitro Comparative Evaluation of Delphinium denudatum and Amaranthus spinosus for Anticonvulsant Activity - Abid, Mohd; Shamim, Shamim; Ali, Shadab; Hak, Jiyaul (Indian Journal of Pharmaceutical Education and Research, 2026)
Introduction: 50 million people worldwide are affected by epilepsy, and a significant proportion suffer from side effects or respond poorly to drugs. With an established use in neurology, Delphinium denudatum (DDE) and Amaranthus spinosus (ASE) still need further studies on their anticonvulsant abilities. Materials and Methods: Hydroethanolic extracts were prepared from DDE roots and ASE leaves. Toxicity was evaluated in albino Wistar rats. Anticonvulsant activity was assessed in Swiss albino mice using the Maximal Electroshock Seizure and Pentylenetetrazole models. GABA levels were analyzed via paper chromatography post-treatment. Doses of 200 and 400 mg/kg were administered. In C1, mice received 100 mg/kg extract and 200 mg/kg phenibut; Diazepam served as the standard in the control group. Results: No toxicity or mortality was observed up to 2000 mg/kg. In the MES model, 400 mg/kg of DDE and ASE extracts significantly reduced tonic hind limb extension (p<0.05), with Combination C2 being the most effective. Both extracts (200 and 400 mg/kg) suppressed PTZ-induced seizures and reduced convulsion duration. Combination C2 improved survival and restored GABA levels close to normal (p<0.01), comparable to Diazepam. Discussion: DDE extract had powerful anticonvulsant effects that may result from GABA and sodium channel activity, whereas ASE extract protected the brain by being an antioxidant. By combining different plant extracts, both therapies outlined the promising effects of natural anticonvulsants. Conclusion: The study concludes that DDE and ASE, especially in combination, exhibit significant anticonvulsant activity, supporting their potential as natural alternatives for epilepsy management.
Keywords: Delphinium denudatum; Amaranthus spinosus; Anticonvulsant activity; Epilepsy; GABA modulation; PTZ and MES models